SMALL MODULAR REACTORS IN THE NUCLEAR ENERGY SECTOR OF THE REPUBLIC OF BULGARIA – ADVANTAGES IN IMPLEMENTATION AND CHALLENGES IN THEIR LICENSING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Over the past four to five years, intensive development has been observed in Central and Eastern Europe of the American nuclear company NuScale - a world leader in the design of small modular reactors. Initiatives to expand the use of nuclear energy and the advancement of technologies in this production are supported and led by the United States of America government. In the article, the author analyzes the prospects of small modular reactors as an eco-innovative technology in nuclear energy, which allows the construction of reliable, clean, safe and economically advantageous energy sources for future generations. Their place in the national energy policy of the Republic of Bulgaria is examined and to what extent the country is interested in their implementation. When compared, the progress in countries such as Romania and Poland is tangible and can be useful to the country. At this stage, the implementation of NuScale's small modular reactors technology in our country is still being studied and evaluated within the framework of the Memorandum of Understanding signed in 2020. It is known that nuclear projects are associated with radiation and environmental risks and the process of their licensing by the national nuclear regulatory authority - the Nuclear Energy Agency is complex and lengthy. The main points of licensing according to the Bulgarian nuclear legislation are presented and the changes that need to be made to the current licensing regimes in order to facilitate the introduction of small modular reactors into operation. The possibilities of international cooperation are also examined to help the process of their licensing.